2003
DOI: 10.1007/s00595-003-2546-y
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen to Detect Hepatic Metastases of Colorectal Cancers

Abstract: The CEA levels in bile, mesenteric venous blood, and peripheral venous blood were increased in patients with CRC and liver metastases. The detection of elevated CEA levels in bile taken at surgery did not herald metachronous hepatic metastases in CRC patients without liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Regarding the portal CEA levels as a prognostic indicator in colorectal cancer, Kutun et al [14] reported that the CEA levels in portal venous blood in the patients with metachronous liver metastases were not significantly different from the cases that did not develop hepatic recurrence, thus concluding that measuring portal CEA levels cannot identify patients at high risk of hepatic recurrence. Tabuchi et al [15], among 94 patients with resectable colorectal cancer, found that the survival curve of the group with normal portal CEA (<5 ng/ml) was significantly better than that of the group with abnormal levels, and the 5-year survival rates were 69% and 41.2%, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the portal CEA levels as a prognostic indicator in colorectal cancer, Kutun et al [14] reported that the CEA levels in portal venous blood in the patients with metachronous liver metastases were not significantly different from the cases that did not develop hepatic recurrence, thus concluding that measuring portal CEA levels cannot identify patients at high risk of hepatic recurrence. Tabuchi et al [15], among 94 patients with resectable colorectal cancer, found that the survival curve of the group with normal portal CEA (<5 ng/ml) was significantly better than that of the group with abnormal levels, and the 5-year survival rates were 69% and 41.2%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Yeatman [13] was among the first that suggested biliary concentration of CEA as a sensitive marker of occult hepatic metastases. Since then, other authors have also evaluated the role of bile CEA as well as peripheral and mesenteric venous blood CEA levels, in prediction of hepatic metastases and prognosis in colorectal cancer patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study with a cutoff of 10 ng/ml, Dorrance et al 5 reported that even though bile CEA taken intraoperatively is a sensitive indicator of occult hepatic metastases, it is not a reliable prognostic indicator, as the accuracy was not higher than 72%. Kutun et al 10 also reported that biliary CEA levels cannot be used to identify patients at high risk of hepatic recurrence.…”
Section: Discussionmentioning
confidence: 96%
“…Kutun et al 10 reported that the CEA levels in portal venous blood were not significantly different in patients with metachronous liver metastases and those without hepatic recurrence. They concluded that measuring portal CEA levels cannot identify patients at high risk of hepatic recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation